A STUDY ON FIVE QUR’ANIC TRANSLATIONS BY NON-MUSLIMS OF THE INDIAN SUB-CONTINENT - Muthuvallur, Luckman (Tanzil: Jurnal Studi Al-Quran, 2024)
The Holy Quran has been translated into almost every language of the world, and India is also credited for being translated into the majority of its languages—these translations from Muslims and non-Muslims. The legitimacy of the translation of the Quran is widely disputable among Muslim scholars. Though most Muslims do not consider Quran translation to be legal under a theological base, it does aid in conveying the divine message to non-Arabic speakers. The driving force of non-Muslim translations that occurred in the Indian sub-continent is the vision of conveying the message of the Quran and the intelligent discussion within different religions and faiths. The Western oriental translations were criticized for failing to capture the original meaning, while the translations by Indians and Eastern scholars were praised for accurately conveying the text’s content and failed to be commonly acknowledged and narrated by the history due to the lack of consistent studies and research. It is a fact that the contribution of non-Muslims to the Quranic study didn’t get needed attention by researchers. This Paper aims to study five Quran translations compiled by non-Muslim scholars of the Indian sub-continent, using the Qualitative method. The results of this research show that there is an impact that these translations can make in the social and religious domain in India.